Significative whitening action of five whitening toothpastes - Gutiérrez llave, Margot (2009)
One of the main concerns of patients is to improve their dentaI aesthetics through teeth whitening, which is why there is a big quantity of products in the market that tries to satisfy this requirement with whitening toothpastes offer. To determinate whitening clinic effect of 5 toothpastes in dental teeth, they were arranged 5 treatment groups for each toothpaste conformed for 5 students and a control group. Subjects were betweeii 18 and 25 years. Colour was evaiuated with Vita Bleaching Shade Guide at the beginning and after 7 weeks through direct observation. Subjects were instructed to brush their teeth using the same toothbrush and the same technique too. There were few changes of colour for toothpaste used, in the experimental as the control group.It was found statistically significant changes of colour between pre and post test in 2 toothpastes (Colgate Max White and Crest Peroxide) (p=0.035). There was not obtained significant differences between whitening toothpaste and control group (p=0.549). As a conclusion, toothpastes used (5 whitening paste and one control paste) made changes on the teeth analyzed, only Colgate Max White y Crest Peroxide produce a significant whitening action on the colour variation. However there was not found a real whitening action behveen experimental and control toothpaste.